Syllable-Initial Phonemes Affect Neural Entrainment to Consonant-Vowel Syllables - Cucu, M. Oana; Kazanina, Nina; Houghton, Conor (Frontiers in Neuroscience, 2022)
Neural entrainment to speech appears to rely on syllabic features, especially those pertaining to the acoustic envelope of the stimuli. It has been proposed that the neural tracking of speech depends on the phonemic features and that some phonemes may provide more effective tracking. In the present electroencephalography experiment, we examined data from twenty-five participants to investigate neural entrainment to near-isochronous stimuli comprising syllables beginning with different phonemes. We measured the inter-trial phase coherence of neural responses to these stimuli and assessed the relationship between this coherence and acoustic properties of the stimuli designed to quantify their ``edginess''. We found that entrainment was different across different classes of the syllable-initial phoneme and that entrainment seemed to depend on the amount of ``edge'' in the sound envelope. In particular, the best edge marker and predictor of entrainment was the latency of the maximum derivative of each syllable.